A multi-dimensional Interval Reduction test. (2nd May 2007) - Wu, Jia-Hwa; Chu, Chih-Ping
Two-dimensional arrays occur quite frequently in real programmes. In general, for multi-dimensional arrays under constant bounds, the Lambda test is an efficient data dependence method to check whether there exist real solutions. In this paper, we propose a multi-dimensional Interval Reduction (IR) test. The multi-dimensional IR test can be applied towards testing whether there are integer solutions for multi-dimensional arrays under constant limits, increasing the testing precision and exploiting the degree of loop parallelisation and vectorisation. Experiments with benchmarks showing the effects of the multi-dimensional IR test are also presented.